Internal medicine residency program director perceptions of USMLE Step 1 pass/fail scoring: A cross-sectional survey. Issue 15 (16th April 2021) - Mun, Frederick; Scott, Alyssa R.; Cui, David; Chisty, Alia; Hennrikus, William L.; Hennrikus, Eileen F.
Abstract : Abstract: The United States Medical Licensing Examination Step 1 will transition to a pass/fail exam starting no earlier than January 2022. Internal medicine residency programs will need to adapt to these changes. The purpose of this study was to investigate: internal medicine residency program directors' perceptions on the change of Step 1 to a pass/fail exam, and the impact on other factors considered for internal medicine residency selection. A validated REDCap survey was sent to 548 program directors at active Accreditation Council for Graduate Medical Education internal medicine residency programs. Contact information from the American Medical Association's Fellowship and Residency Electronic Interactive Database was used. The survey had 123 respondents (22.4%). Most internal medicine program directors do not support the pass/fail change. A greater importance will be placed on Step 2 Clinical Knowledge exam, personal knowledge of the applicant, clerkship grades, and audition electives. Allopathic students from less highly regarded medical schools, as well as osteopathic and international students, will be disadvantaged. About half believe that schools should adopt a graded pre-clinical curriculum (51.2%) and that there should be residency application caps (54.5%). Internal medicine program directors mostly disagree with the pass/fail Step 1 transition. Residency programs will need to reevaluate how applicants are evaluated. Other factors, such as Step 2 Clinical Knowledge score, personal knowledge of the applicant, grades in clerkships, and audition rotations will now be emphasized more heavily. Abstract : Supplemental Digital Content is available in the text